Islamic Chaplaincy - Sadiq, Rehanah (International Journal of Human and Health Sciences (IJHHS), 2024)
This talk takes the listener into the world of chaplaincy and spiritual care. It offers an insight into the impact it has on patients and families, and shows how holistic care is incomplete without it. Focusing on Muslim Chaplaincy, it uses real life cases to illustrate the healing, uplifting and calming effects it has on the wellbeing of patients and their relatives. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S27